Facility management demand theory: Impact of proactive maintenance on corrective maintenance. Issue 4 (2nd September 2019) - Che-Ani, Adi Irfan; Ali, Roslan
Abstract : Purpose: This study aims to confirm the inverse relationship between scheduled corrective maintenance (SCM) and corrective maintenance (CM) in health-care facility management. That is, the higher the SCM, the lower the demand for CM, and the lower the SCM, the higher the demand for CM. Furthermore, the study shows the importance of SCM as compared with CM in healthcare facilities. Design/methodology/approach: This study investigated 28 services in facility engineering services for an exploratory study by using the open-ended approach of the grounded theory. Five years of data with a total of 20, 480 SCM work orders and 84, 837 CM work orders were extracted from the central management information system database. Data were analyzed using the Statistical Package for the Social Sciences program. Data were presented in the form of mathematical scores using descriptive statistics and correlation test to elaborate the variable characteristics and make conclusions. Findings: This study provides empirical insights about the effectiveness of proactive maintenance in reducing breakdowns for systems or equipment in health-care facilities. Findings suggest that increasing SCM will reduce CM demands. Research limitations/implications: The location approach, with restrictions to the comparison between CM and SCM, still allows for exploration, especially on the factors that can reduce the demand for correction. These factors include planned preventive maintenance, work flow process, level of competency of maintenance workers and health-care maintenance strategic planning. Practical implications: Proactive maintenance is important in preventing dangerous occurrences in hospitals. Reducing breakdowns increases customer satisfaction. Therefore, this study shows implications to health-care maintenance organizations in the context of business strategic development. Originality/value: Data are crucial in proving a hypothesis. This study confirms the evidence of facility management demand theory and highlights the inverse relationship between SCM and CM.